PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING PADA GURU DALAM MENINGKATKAN PEMANFAATAN DIGITALISASI DI SMP 1 BONTONOMPO - Ninik Rahayu Ashadi; Ismail Aqsha; Suwahyu, irwansyah; Dwi Rezky Anandari Sulaiman (Paramacitra Jurnal Pengabdian Masyarakat, 2024)
The aim of training on the use of E-Learning-based learning media for teachers in increasing the use of digitalization at SMP 1 Bontonompo is to enrich teachers' insight in utilizing various types of media currently available in their teaching process. Teachers who are still monotonous in their learning process are given training so they can take advantage of current technological developments. This will certainly have a good impact on students. The implementation method for this service is through lectures, questions and answers, as well as direct practice in using e-learning based learning media. The results obtained in this training are that subject teachers or training participants are able to utilize E-leaning-based learning media as digital learning media, as well as creating innovative spaces in the learning process by utilizing technology. The implementation of this training also motivates teachers to be more proactive in developing media and learning materials. With additional learning methods applied, it is hoped that student learning outcomes and teacher insight will increase. By facilitating the internet in learning, access to various worlds and fields of knowledge will become wider so that it will increase students' knowledge that is not only obtained in class.